Protected landscape elements in the European Union and the Hungarian effects of the regulation in the look of the kurgans - Rákóczi, Attila; Barczi, Attila (JOURNAL OF LANDSCAPE ECOLOGY, 2014)
There was a significant alteration in the CAP and in the EU regulations in agriculture and as a result of this in Hungarian regulations too. The kurgans were declared protected by law in 2010 (GAEC) in accordance with crosscompliance requirements. Kurgans are significant landscape elements of the Great Hungarian Plain/Carpathian Basin. The oldest mounds may be even 6,000 years old. These human-made formations are valuable –among others-because of their archeological, cultural, historical, botanical, pedological and landscape significance. They significantly decreased in number in the past decades since they became part of the cultivated areas. There have been several unsuccessful attempts to protect them by bringing them under regulation. However, owing to an EU agrarian regulation kurgans (Cumanian mounds) were designated as protected landscape elements which became the condition of payment of direct support. In our research we focus on the impacts of the regulation through the field studies performed in Békés County, which makes it possible to assess the changes in state of the mounds. It is carried out through full- and representative samplings but monitoring methods are also used. The regulation applies to 185 mounds in Békés County, 98 of them in 2012, 78 in 2011 and 40 in 2012 were cultivated. The number of cultivated mounds decreased to 24 by 2013. Studying the results it can be stated that in opposition to the previously less efficient attempts to regulate them, due to the latest regulation the mound protection became more efficient in the last few years. This indicates that the mounds can be saved from deterioration, and the multifuncionality, eco-potential and diversity of the countryside can be maintained.
Keywords: landscape protection; national value; cultural history; common agricultural policy; cross compliance